Pulp polyp in children: polip pulpa pada anak - Difa Dirgantara; Siti Fatimah; Ervina tyawarman; Alfiyah Pujiyati; Leny Sang Surya,; Hanim Khalida Zia; Oniel Syukma Pertiwi (Makassar Dental Journal, 2024)
Pulp polyps are known as chronic hyperplastic pulpitis. Clinically, these polyps appear as proliferative red masses mostly associated with the occlusal surfaces of non-vital molars in individuals with higher immunity and are caused by long-standing low-grade infections. Radiographically, the pulp lesion does not show any periapical changes, but delay in treatment can lead to the spread of inflammation into the periodontal ligament through the apical foramen. This case report aims to find out and understand the polyps that occur in paediatric patients who are treated at RSGM Baiturrahmah Padang. One of the managements of pulppolyps is by performing root canal treatment as well as in the diagnosis of pulpitis, only preceded by the removal of polyp tissue. In conclusion, the prognosis of pulp polyps is very good. There is no risk of recurrence after definitive treatment is given.